Analysis of Poverty Determination in Madura 2010 - 2019 - Kamilah Kamilah; Teguh Hadi Priyono; Duwi Yunitasari; Sunlip Wibisono; Rafael Purtomo Somaji; Nanik Istiyani; Edy Santoso (MediaTrend, 2022)
One of the largest’s poverty percentage in East Java Province is on Madura insland.The average percentage of poverty in district on Madura Island is higher than thepercentage of poverty in East Java Province. Based on this, it is known that the poverty rate in Madura is above East Java Province, reaching more than 20 percent. 2022This study aims to determine the effect of the independent variables of economicgrowth, Unemployment Rate, Inequality of Income Distribution on Poverty Levelson Madura Island. In this case, the data used is panel data which is a combinationof the time series, namely 2010 – 2019 and the latitude series of 4 districts inMadura. The data analysis method used in this research is panel data regression.The results of this study are the variable economic growth (X1) has a negative andsignificant effect on poverty in Madura Island. The Variable Unemployment Rate(X2) has a positive and insignificant effect on poverty in Madura Island. Incomedistribution inequality variable (X3) has a negative and significant effect on povertyin Madura Island